(untitled) (Eurasian Journal of Engineering and Technology, 2022)
Electronic simulators designed for teaching computer science in educational institutions, including higher educational ones, can be classified according to various grounds: by the age of the studied science and students, by the degree of their mastery of foreign languages and information and communication technologies, by the need for internet connection and by the device computer, mobile device that ensures the operation of the program. Depending on the student’s native language, trainers can be divided into universal as well as trainers specially designed for speakers of a particular language, taking into account the usual difficulties encountered in the study of foreign languages and information and communication technologies and mistakes made during the test.